Methods of protection of currency risks - Lymarenko, Ksenіya (My University, 2014)
All participants in the international currency market incur currency risks, i.e. risk of loss in the exercise of those or other operations. Currency risks are associated with inflation and currency fluctuation. If exchange rates were fixed, there would be no currency risk. The objective basis of currency risk is that in the long run, exchange rates depend on the economic situation of different countries, but in short - on the decisions of public authorities on economic issues, speculative transactions, rumors and expectations, political events, and, finally, on the wrong solutions of dealers.
Keywords: обмінний курс; exchange rate; валютний ризик; currency risk